196 III The Function Spaces of Hydrodynamics
III.4.1 Bounded Domains
The simplest situation occurs when Ω is star-shaped (with respect to the
origin, say). For ρ ∈ (0, 1) we know from Exercise II.1.3 that Ω
(ρ)
⊂ Ω. Thus,
given a vector v ∈
b
H
1
q
(Ω), by extending it by zero outside Ω, we deduce that
the family of vectors v
ρ
(x) ≡ v(x/ρ), x ∈ R
n
, belongs to
b
H
1
q
(Ω) and is of
compact support in Ω. Set
h
0
= min
x∈∂Ω
|x|, ε(ρ) = h
0
(1 −ρ)/2
and consider the mollification (v
ρ
)
ε(ρ)
≡ V
ρ
. By the results ofSection II.2
on regularizations we obtain that, for each ρ ∈ (0, 1), V
ρ
∈ D(Ω) and that
V
ρ
→ v in W
1,q
(Ω) as ρ → 1, for all q ∈ [ 1, ∞). Therefore, for these values
of q,
b
H
1
q
(Ω) ⊂ H
1
q
(Ω) and the two spaces coincide.
Using an idea of Bogovski
˘
i (1980, Lemma 4), this result can be generalized
to a fairly reach class of bounded domains. Specifically, we have the following.
Theorem III.4.1 Assume that the bounded domain Ω ⊂ R
n
, n ≥ 2, is
the union of a finite number of domains Ω
i
each of which is star-shaped with
respect to an open ball B
i
with B
i
⊂ Ω
i
(e.g., Ω satisfies the cone condition).
5
Then
b
H
1
q
(Ω) = H
1
q
(Ω).
Proof. Let us first consider the case q ∈ (1, ∞). Given v ∈
b
H
1
q
(Ω), let
{v
k
} ⊂ C
∞
0
(Ω) be a sequence approximating v in W
1,q
(Ω) and denote by
w
k
a solution to (III.3.2) with f = −∇ · v
k
. Since f satisfies (III.3.1 ), by
Theorem III.3.1 w
k
exists, belongs to W
1,q
0
(Ω), and can be taken to b e of
compact support i n Ω. The functions u
k
= v
k
+ w
k
, k ∈ N, are thus diver-
gence free and of compact support in Ω. Furthermore, using (III.3.3) for w
k
,
we have
ku
k
−vk
1,q
≤ kv
k
−vk
1,q
+ kw
k
k
1,q
≤ kv
k
−vk
q
+ ck∇· v
k
k
q
with c independent of k. Since ∇ · v = 0, it fo llows that
k∇· v
k
k
q
→ 0 as k → ∞,
and so the previous inequality furnishes
u
k
→ v in W
1,q
(Ω), as k → ∞.
Let (u
k
)
ε
be the regularization of u
k
. For sufficiently small ε, (u
k
)
ε
belongs
to D(Ω) and approaches u
k
in W
1,q
(Ω) (see Section II.2 and Exercise II.3.2),
which proves v ∈ H
1
q
(Ω). Let us now prove H
1
1
(Ω) =
b
H
1
1
(Ω). To this end,
5
See Remark III.3.4 and Remark III.3.5.